2020
DOI: 10.1186/s13098-020-00618-z
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA CDKN2B-AS1 regulates high glucose-induced human mesangial cell injury via regulating the miR-15b-5p/WNT2B axis

Abstract: Background Long non-coding RNA cyclin-dependent kinase inhibitor 2B antisense RNA 1 (CDKN2B-AS1) has been reported to be related to diabetic nephropathy (DN) progression. However, the regulatory mechanisms of CDKN2B-AS1 in DN are unclear. Methods High glucose (HG) was used to induce human mesangial cells (HMCs) for establishing the DN model. Expression levels of CDKN2B-AS1, microRNA (miR)-15b-5p, wingless-Type family member 2B (WNT2B) mRNA in serum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 31 publications
1
13
0
Order By: Relevance
“…Similarly, a previous study revealed that forced expression of miR-15b-5p restrained HG-triggered apoptosis of podocytes and inflammatory responses and repressed oxidative stress damage[ 43 ]. The miR-15b-5p mimic repressed the viability and inflammation of HG-treated HMCs, as previously shown[ 42 ]. The findings show that silencing XIST inhibits HG-induced RTEC pyroptosis in vitro by promoting miR-15b-5p.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Similarly, a previous study revealed that forced expression of miR-15b-5p restrained HG-triggered apoptosis of podocytes and inflammatory responses and repressed oxidative stress damage[ 43 ]. The miR-15b-5p mimic repressed the viability and inflammation of HG-treated HMCs, as previously shown[ 42 ]. The findings show that silencing XIST inhibits HG-induced RTEC pyroptosis in vitro by promoting miR-15b-5p.…”
Section: Discussionsupporting
confidence: 78%
“…qRT-PCR showed that miR-15b-5p in the DN models was significantly lower but increased after silencing XIST. Accordingly, miR-15b-5p was found to be downregulated in the serum of DN patients and in HG-treated HMCs[ 42 ]. XIST can adsorb and bind to miR-15b-5p to reduce miR-15b-5p expression in DN.…”
Section: Discussionmentioning
confidence: 99%
“…showed that WNT2B was upregulated in DN mice and HG-induced mesangial cells, which might accelerate DN progression by enhancing cell proliferation, inflammation, and ECM accumulation [ 30 ]. Also, lncRNA CDKN2B increased WNT2B expression to promote HG-induced HMC proliferation and ECM accumulation via sponging miR-15b-5p [ 31 ]. In this, we confirmed that WNT2B could be targeted by miR-147a, and its expression was positively regulated by lncRNA HOTAIR.…”
Section: Discussionmentioning
confidence: 99%
“… 36 Moreover, Wnt2b is up‐regulated in serum of patients with DN and mesangial cells cultured in high glucose environment, and high glucose treatment could enhance the inflammation and extracellular matrix via activating the Wnt2b/β‐catenin pathway induced by two different long non‐coding RNAs, providing new mechanisms for understanding the development of DN and promising target for its treatment. 37 , 38 …”
Section: Roles Of Wnts In T2dm and Related Complicationsmentioning
confidence: 99%
“…The expression of Wnt2b and mediated canonical Wnt pathway is induced and inversely correlated with insulin expression in islets of T2DM patients, indicating inhibition of this pathway might be a new route to prevent the failure of β‐cells 36 . Moreover, Wnt2b is up‐regulated in serum of patients with DN and mesangial cells cultured in high glucose environment, and high glucose treatment could enhance the inflammation and extracellular matrix via activating the Wnt2b/β‐catenin pathway induced by two different long non‐coding RNAs, providing new mechanisms for understanding the development of DN and promising target for its treatment 37,38 …”
Section: Roles Of Wnts In T2dm and Related Complicationsmentioning
confidence: 99%